Hepatotoxicity induced by arsenic trioxide: clinical features, mechanisms, preventive and potential therapeutic strategies - Wen, Jun; Li, Aiwen; Wang, Ziliang; Guo, Xiaoxiao; Zhang, Gaoling; Litzow, Mark R.; Liu, Qiuju (Frontiers in Pharmacology, 2025)
Arsenic trioxide (ATO) has shown substantial efficacy in the treatment of patients with acute promyelocytic leukemia, and the utilization of ATO as a potential treatment for other tumors is currently being investigated; thus, its clinical application is becoming more widespread. However, the toxicity of ATO has prevented many patients from receiving this highly beneficial treatment. The clinical features, mechanisms, and preventive measures for ATO hepatotoxicity, as well as potential curative strategies, are discussed in this review. This review not only discusses existing drugs for the treatment of hepatotoxicity but also focuses on potential future therapeutic agents, providing forward-looking guidance for the clinical use of small molecule extracts, trace elements, antidiabetic drugs, and vitamins.